2007
DOI: 10.1371/journal.pone.0000224
|View full text |Cite
|
Sign up to set email alerts
|

Plant Carbohydrate Scavenging through TonB-Dependent Receptors: A Feature Shared by Phytopathogenic and Aquatic Bacteria

Abstract: TonB-dependent receptors (TBDRs) are outer membrane proteins mainly known for the active transport of iron siderophore complexes in Gram-negative bacteria. Analysis of the genome of the phytopathogenic bacterium Xanthomonas campestris pv. campestris (Xcc), predicts 72 TBDRs. Such an overrepresentation is common in Xanthomonas species but is limited to only a small number of bacteria. Here, we show that one Xcc TBDR transports sucrose with a very high affinity, suggesting that it might be a sucrose scavenger. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
342
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(355 citation statements)
references
References 122 publications
10
342
1
2
Order By: Relevance
“…Therefore, the reduction in ability of the GAPDH-defective mutant to utilize available carbohydrates in the host reduces its growth, with consequences for its aggressiveness. Consistent with this, it has recently been demonstrated that glucose and sucrose utilization is required for full virulence in Xcc (Blanvillain et al, 2007;Lu et al, 2007b). Previously, we have shown that an Xcc ppsA (a gene encoding phosphoenolpyruvate synthase, the key enzyme in gluconeogenesis) mutant, which has lost the capability to utilize pyruvate and C 4 dicarboxylates as carbon sources, has limited growth in host tissues and significantly reduced virulence compared with the wildtype .…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, the reduction in ability of the GAPDH-defective mutant to utilize available carbohydrates in the host reduces its growth, with consequences for its aggressiveness. Consistent with this, it has recently been demonstrated that glucose and sucrose utilization is required for full virulence in Xcc (Blanvillain et al, 2007;Lu et al, 2007b). Previously, we have shown that an Xcc ppsA (a gene encoding phosphoenolpyruvate synthase, the key enzyme in gluconeogenesis) mutant, which has lost the capability to utilize pyruvate and C 4 dicarboxylates as carbon sources, has limited growth in host tissues and significantly reduced virulence compared with the wildtype .…”
Section: Discussionsupporting
confidence: 78%
“…XCC3358 was recently described as one of 72 TonB-dependent receptors in the phytopathogen Xanthomonas campestris pv. campestris (Xcc) transporting sucrose with high affinity, and found to be required for full pathogenicity on Arabidopsis (26). Overall, the presence of multiple TonB transporters may account for the large abundance of Sphingomonas spp.…”
Section: Plant-associated Lifestylementioning
confidence: 99%
“…TonBdependent channels were originally identified in the context of iron transport, but have since been associated with the transport of a large variety of compounds (Schauer et al, 2008). Of particular interest is their newly recognized association with degradation of polymers and complex carbohydrates (Blanvillain et al, 2007;Martens et al, 2009). Several of the TonB-dependent channels in Polaribacter sp, MED152 were associated with predicted peptidases and glycosyl hydrolases (González et al, 2008), suggesting they may be involved in utilization of high molecular weight substrates in this organism.…”
Section: Nutrient Acquisition Strategies Of Monterey Bay Rhodobacteramentioning
confidence: 99%